Aislamiento y caracterización bioquímica de la α-glucosidasa II del hongo patógeno Candida albicans - Rangel Alfaro, Carlos Alberto; Mora-Montes, Héctor Manuel; Flores-Martínez, Alberto; Flores Carreón, Arturo (Acta Universitaria, 2011)
Alpha-glucosidase II participates in N-linked glycosylation of proteins. A soluble 47 kDa Î±-glucosidase II has been previously isolated from C. albicans; however, bioinformatics analysis indicate that native enzyme has a molecular mass of 100 kDa. In this study we assessed the effect of protease inhibitors on intracellular distribution of Î±-glucosidase II. Despite there was not a significant change in the enzyme distribution, Î±-glucosidase II activity was associated to a 83 or 47 kDa polypeptide in absence or presence of inhibitors, respectively. Soluble 83-kDa protein was purified by conventional methodology and its biochemical characteristics were similar to those reported for the 47 kDa enzyme. Thus, these results indicated the 83 kDa protein is an Î±-glucosidase II and also suggested it is a precursor of the 47 kDa enzyme previously reported.
Keywords: Array; Array; Array; Array